2010
DOI: 10.1371/journal.pntd.0000630
|View full text |Cite
|
Sign up to set email alerts
|

Nodular Worm Infection in Wild Chimpanzees in Western Uganda: A Risk for Human Health?

Abstract: This study focused on Oeosophagostomum sp., and more especially on O. bifurcum, as a parasite that can be lethal to humans and is widespread among humans and monkeys in endemic regions, but has not yet been documented in apes. Its epidemiology and the role played by non-human primates in its transmission are still poorly understood. O. stephanostomum was the only species diagnosed so far in chimpanzees. Until recently, O. bifurcum was assumed to have a high zoonotic potential, but recent findings tend to demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 26 publications
(38 reference statements)
5
48
0
1
Order By: Relevance
“…Nematode helminths are prevalent in zoo collections and FZP is not an exemption. According to Krief et al (2010), some helminths coexist with wildlife with no obvious pathology; also the screened animals at FZP did not show any clinical signs or pathology which suggests mild to moderate infection at sub clinical level. The current level of hygiene standard at FZP is adequate and should not be allowed to slip to prevent heavy helminth and other parasitic infection.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nematode helminths are prevalent in zoo collections and FZP is not an exemption. According to Krief et al (2010), some helminths coexist with wildlife with no obvious pathology; also the screened animals at FZP did not show any clinical signs or pathology which suggests mild to moderate infection at sub clinical level. The current level of hygiene standard at FZP is adequate and should not be allowed to slip to prevent heavy helminth and other parasitic infection.…”
Section: Discussionmentioning
confidence: 97%
“…Nematode helminths impart negatively on the conservation and health of wildlife (Pedersen et al, 2005;Gillespie, 2006;Hotez et al, 2008). Although it is possible for helminths to coexist with wildlife without obvious pathology (Krief et al, 2010;Ryan et al, 2012) however in some instances, consequent pathology may be more severe (Emikpe et al, 2002;Emikpe et al, 2007;Muller et al, 2010). The stress of captivity and contiguity to humans (Woodford et al, 2002;Wenz et al, 2009) may also contribute to how resistant these animals will be to parasites in captivity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that there was transmission of nodular worm among nonhuman primates and humans and thus primates poised a health risk to people or vice versa (Krief et al, 2010;Ghai et al, 2014). Among Oesophagostomum genus, O. bifurcum, O. stephanostomum, and O. aculeatum, are important due to their potential to infect humans (Ghai et al, 2014).…”
Section: Nodular Worm Infections Caused Bymentioning
confidence: 99%
“…Several cases of cross-species transmissions have been reported between humans and non-human primates, including viruses [Köndgen et al, 2008;Li et al, 2010], bacteria [Rwego et al, 2008;Wolf et al, 2014], blood-borne parasites [Standley et al, 2012], and intestinal parasites [Rwego et al, 2008;Hasegawa et al, 2014;Cibot et al, 2015]. Moreover, the risk of cross-species transmission is increasing because humans and non-human primates share more and more the same habitat [Legesse and Erko, 2004;Krief et al, 2010;Keita et al, 2014;Cibot et al, 2015;Narat et al, 2015], leading to water and food contamination [Legesse and Erko, 2004;Schuster and Visvesvara, 2004;Mossoun et al, 2015] or vector-borne disease transmission [Keita et al, 2014]. For example, zoonotic infections (pathogen agents that cross the barrier between humans and animals) were evidenced for intestinal parasites [Levecke et al, 2015] and herpesvirus [BurgosRodriguez, 2011] via physical contacts between humans and non-human primates, spumavirus such as simian foamy virus via exposure to simian fluids [Greger, 2007], and malaria [Galinski and Barnwell, 2009] via an intermediary host (mosquito bites).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning Oesophagostomum sp. infection, acute pain in the abdomen is the most common manifestation in humans -mimicking appendicitis -but the disease can also be lethal to chimpanzees [Krief et al, 2008[Krief et al, , 2010Centers for Disease Control and Prevention, 2016b]. Wild-born great apes develop clinical signs of oesophagostomosis as soon as they are detained in captivity while the presence of the same parasites often remains asymptomatic in wild animals [Krief et al, 2008].…”
Section: Introductionmentioning
confidence: 99%